TIPOLOGI PENERIMAAN TRANSGENDER DI DALAM KELUARGA (STUDI DI PONDOK PESANTREN WARIA AL FATAH DAN YAYASAN WARIA CRISIS CENTER YOGYAKARTA) - Nur Afni Khafsoh; Inggriana Sahara Bintang; Gibran Zahra Abida Rilana; Mila Khoirunnisa; Rita Dwi Purnama Sari; Ozzy Mahar Pratiwi; Andris Fathu Rahman Shidiq (UIN Walisongo Semarang, 2022)
Transgender is often one of the groups who are vulnerable to living unfit. This is due to its limitations in accessing various things such as education and employment. In addition, their families often don't accept them, even though the family is the strongest fortress in protecting transgender people from violence and oppression. This study looks at how the acceptance of transgender families in the family and identifies the typology of families in accepting transgender family members. This research is qualitative research with data collection techniques and in-depth interviews. The research location was at the Al Fatah Transgender Islamic Boarding Home and the Waria Crisis Center Community in Yogyakarta.The result of this study is that the existence of transgender people is still considered a disgrace to the family so that evictions still occur. The family form is like doing Rukyah, forced marriage. So, many transgender people end up leaving their families. In addition, the typology of families who accept the existence of transgender people can be seen from three factors: education, economy, and religious understanding. Thus, family acceptance is very important in transgender life.